2019
DOI: 10.3390/nano9091301
|View full text |Cite
|
Sign up to set email alerts
|

Application of CuxO-FeyOz Nanocatalysts in Ethynylation of Formaldehyde

Abstract: Composite nanomaterials have been widely used in catalysis because of their attractive properties and various functions. Among them, the preparation of composite nanomaterials by redox has attracted much attention. In this work, pure Cu2O was prepared by liquid phase reduction with Cu(NO3)2 as the copper source, NaOH as a precipitator, and sodium ascorbate as the reductant. With Fe(NO3)3 as the iron source and solid-state phase reaction between Fe3+ and Cu2O, CuxO-FeyOz nanocatalysts with different Fe/Cu ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…In addition, vibrational peaks at around 147, 214, and 644 cm –1 appeared for samples grown on the Cu foil. These additional phonon modes appeared close to 145, 216, 284, and 493 cm –1 can be attributed to the Cu 2 O phase and those close to 298, 330, 346, and 626 cm –1 can be attributed to the CuO phase. These observations indicate the possibility of the facile Cu x O/ZnO ( x = 1, 2) junction formation by postannealing at a temperature as low as 250 °C and are also consistent with the XRD patterns shown in Figure b. From both XRD and Raman analyses, it can be concluded that for depositing single-phase highly c -axis-oriented ZnO films, it may be better to use sonication step(s)-less SILAR process irrespective of the substrate type and postannealing at 250 °C for 1 h is required for facile formation of Cu-oxide/ZnO heterojunction when Cu foil is used.…”
Section: Resultssupporting
confidence: 80%
“…In addition, vibrational peaks at around 147, 214, and 644 cm –1 appeared for samples grown on the Cu foil. These additional phonon modes appeared close to 145, 216, 284, and 493 cm –1 can be attributed to the Cu 2 O phase and those close to 298, 330, 346, and 626 cm –1 can be attributed to the CuO phase. These observations indicate the possibility of the facile Cu x O/ZnO ( x = 1, 2) junction formation by postannealing at a temperature as low as 250 °C and are also consistent with the XRD patterns shown in Figure b. From both XRD and Raman analyses, it can be concluded that for depositing single-phase highly c -axis-oriented ZnO films, it may be better to use sonication step(s)-less SILAR process irrespective of the substrate type and postannealing at 250 °C for 1 h is required for facile formation of Cu-oxide/ZnO heterojunction when Cu foil is used.…”
Section: Resultssupporting
confidence: 80%
“…The results reveal that bivalent copper was quickly reduced to elemental copper in the ball milling process. This also reflects that divalent copper could be easily reduced, which was in good accordance with the previous reports. According to Figure f, characteristic peaks of zinc in the raw materials at 1022.3 and 1045.3 eV correspond to Zn 2p 3/2 and Zn 2p 1/2 in zinc oxide. In the ball milling process, the characteristic peaks of zinc have not changed, indicating stable chemical properties of zinc oxide.…”
Section: Resultssupporting
confidence: 89%
“…1 illustrates, FB500 showed apparent Fe2p peaks at 712.1 eV (Fe 3+ ) and 710.3 eV (Fe 2+ ). 43 The molar ratio of Fe 2+ :Fe 3+ on the surface of FB500 calculated from the peak areas of Fe 2+ and Fe 3 + was 1.48. The presence of Fe in different valences indicated that Fe oxide was formed which should be the source of magnetism.…”
Section: Resultsmentioning
confidence: 97%